2018
DOI: 10.1080/10826084.2018.1517177
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pathways of adolescent cannabis use: Risk factors, outcomes and sex-specific differences

Abstract: Background: Characterizing patterns of adolescent cannabis use (CU), as well as risk factors and outcomes uniquely associated with these pathways is essential for informing treatment and prevention efforts. Yet, few studies have examined these issues among youth at-risk of engaging in problematic cannabis use. Further, research accounting for use of other substances or sex differences in patterns of CU remains exceedingly sparse. Methods: Trajectory-based modeling was used to identify underlying CU pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…Three different U.S. based studies independently found that cannabis use trajectory group status was not predictive of increased anxiety levels or lifetime anxiety diagnosis in adulthood. 28,37,44 For instance, in a cohort of 401 adolescents with chronic, escalating, and low cannabis use, anxiety outcome did not differ across groups at 2-year follow-up (χ 2 = 0.12, df = 2, P = .94). 44 One small study from 1985 focused on the adult population and found 11 out of 97 regular cannabis users were newly diagnosed with anxiety disorders at follow-up 6 to 7 years later, but this increase in prevalence was not considered to be statistically significant.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Three different U.S. based studies independently found that cannabis use trajectory group status was not predictive of increased anxiety levels or lifetime anxiety diagnosis in adulthood. 28,37,44 For instance, in a cohort of 401 adolescents with chronic, escalating, and low cannabis use, anxiety outcome did not differ across groups at 2-year follow-up (χ 2 = 0.12, df = 2, P = .94). 44 One small study from 1985 focused on the adult population and found 11 out of 97 regular cannabis users were newly diagnosed with anxiety disorders at follow-up 6 to 7 years later, but this increase in prevalence was not considered to be statistically significant.…”
Section: Resultsmentioning
confidence: 95%
“…28,37,44 For instance, in a cohort of 401 adolescents with chronic, escalating, and low cannabis use, anxiety outcome did not differ across groups at 2-year follow-up (χ 2 = 0.12, df = 2, P = .94). 44 One small study from 1985 focused on the adult population and found 11 out of 97 regular cannabis users were newly diagnosed with anxiety disorders at follow-up 6 to 7 years later, but this increase in prevalence was not considered to be statistically significant. 24 In another study of 2,429 U.S. youth, latent growth modeling suggested GAD symptoms at 10-year follow-up were predicted by higher probability of cannabis and tobacco couse, but not cannabis use alone (intercept estimate = −0.01, slope estimate = 0.00, P > 0.05).…”
Section: Resultsmentioning
confidence: 95%
“…The majority of the sample (90%) reported some use, even if minimal, of either alcohol, cigarettes, or other drugs at time of screening. Additional information on participant selection can be found in prior publications with this cohort (Duperrouzel et al, in press; Hawes, Trucco, Duperrouzel, Coxe, & Gonzalez, 2018; Lopez-Quintero et al, 2018; Ross, Graziano, Pacheco-Colón, Coxe, & Gonzalez, 2016). Participants were also between the ages of 14 and 17 at baseline, and able to read and write English.…”
Section: Methodsmentioning
confidence: 99%
“…Age, gender, and socioeconomic factors were found to be associated with marijuana use in previous studies (Hawes, Trucco, Duperrouzel, Coxe, & Gonzalez, 2019;Widome, Wall, Laska, Eisenberg, & Neumark-Sztainer, 2013), and so we controlled for these demographic characteristics. Age was measured by years (ratio scale), gender was coded as a binary variable (male = 1, other = 0), and socioeconomic status was measured by a self-reported status of receiving free or reduced lunch at school (yes = 1, no = 0).…”
Section: Control Variablesmentioning
confidence: 99%